Manajemen Pembinaan Karakter Mulia - Akhmad Alim; Ahmad Sastra; M. Ikbar Muhyi Maulani (Al-Liqo: Jurnal Pendidikan Islam, 2022)
The background of this research is that there are still many students arriving late to class, falling asleep in class, bullying among their friends, impolite behavior towards teachers, older students not loving younger students, not caring for the environment. well, and there are many other undisciplined things. The purpose of this study is the implementation of noble character development management, knowing the supporting and inhibiting factors in the implementation of noble character development. This study uses a descriptive qualitative research method. The results of this study are (1) noble character-building management planning, (2) the management mandate of noble character development, (3) the implementation of noble character development management, (4) the factors that become supporters and obstacles in the implementation of noble character development.